1996
DOI: 10.1074/jbc.271.28.16494
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Mitogen-activated Protein Kinase and Na+/H+ Exchanger in Human Platelets

Abstract: Platelets are terminally differentiated cells that exhibit rapid phosphorylation of many proteins upon agonist-induced activation. Thus, platelets are a good model system to study signal transduction events that are not regulated by gene expression of proteins.Mitogen-activated protein kinases (MAPKs) 1 comprise a family of 40 -45-kDa protein serine/threonine kinases that are activated by many extracellular stimuli, including growth factors and hormones. MAPKs require phosphorylation on both threonine and tyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
64
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 47 publications
4
64
2
Order By: Relevance
“…Those similarities provide evidence to suggest that ERK may be a direct proximal component of an NHE regulatory pathway [5,6]. There is a growing awareness that tyrosine phosphorylation cycles are critical in regulating NHE activities in a number of cell types [6][7][8][9][10], as has also been shown for ERK [11]. Other studies have demonstrated that NHE and ERK activities are modulated by overlapping upstream enzymes, including phosphoinositide 3h-kinase (PI-3K), phospholipase Cγ, and PKC [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Those similarities provide evidence to suggest that ERK may be a direct proximal component of an NHE regulatory pathway [5,6]. There is a growing awareness that tyrosine phosphorylation cycles are critical in regulating NHE activities in a number of cell types [6][7][8][9][10], as has also been shown for ERK [11]. Other studies have demonstrated that NHE and ERK activities are modulated by overlapping upstream enzymes, including phosphoinositide 3h-kinase (PI-3K), phospholipase Cγ, and PKC [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 87%
“…Moreover, the signal initiated by AVP was sensitive to genistein, a broad-spectrum inhibitor of tyrosine kinases [6]. The study of Aharonovitz and Granot [6] specifically supported a role for MEK and a tyrosine kinase in the activation of platelet NHE by AVP, but did not address the role of other molecules in the ERK cascade in this process. More recently, Bianchini et al [25] presented data to support a role for ERK in activating NHE type 1 in fibroblast cells.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations